Holub József és a Tagányi-könyvtár Pécsre kerülése: Egy „vidéki” történészprofesszori egzisztencia lehetőségfeltételei az 1920-as évek elején (II. közlemény) - Szeberényi, Gábor (Per Aspera ad Astra, 2015)
The second part of the study reveals the potential adventages and limits of professional opportunities lay before József Holub during the Spring and Summer of 1923, and tries to determine those personal and professional considerations which finally led to his decision to accept the proffersorship at the Elisabeth University in the Autumn of the year. In the background of Holub’s personal choices, the paper also tries to reconstruct thoroughly the exact „institutional circumstances” and processes of decision making related to the filling of the (semi-)vacant department of Hungarian History of the University, which was in an in-transit state during 1923, and moved from Budapest to Pécs till the end of the year, while left behind many of its lead professors in the capital. Within this framework the author tries to point out that the acception of History professorship at the Elisabeth University was a good, but not necessarily the only (or even the best) choice for Holub in 1923.